Emisja gazów cieplarnianych w Polsce i w województwie lubuskim w latach 2010-2015 = Emissions greenhouse gas in Poland and in the lubuskie in years 2010-2015 - Słobodzian-Ksenicz, Oryna; Jasiewicz, Marzena; Polus, Dominik (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Emissions of greenhouse gases and their precursors is one of the most im-portant problems of the twenty-first century. The paper contains an analy-sis of the emissions of these pollutants by sector KOBIZE in Poland and lubuskie in 2010-2015.In the structure of greenhouse gas emissions it has the biggest share of the sector 1.Energy, 4. Agriculture and 6. Sludge. GHG emissions tend downward with the exception of CH4. The total GHG emis-sions in terms of CO2 ekw.i precursors GC in Poland and lubuskie despite fluctuations to decline.
Keywords: gazy cieplarniane; globalne ocieplenie; ditlenek węgla; metan; tlenek diazotu; ditlenek siarki; lubuskie; green house gase; global warming; carbon dioxide; methane; nitrous oxide; sulfur dioxide